Caracterização da Alteração Hidrotermal Micácea do Tipo Greisen e dos Reequilíbrios de Baixa Temperatura em Áreas Graníticas: o Exemplo do Distrito Estanífero de Encruzilhada do Sul, RS - TEIXEIRA, ROBERTO DOS SANTOS; FRANTZ, JOSÉ CARLOS; MEXIAS, ANDRÉ SAMPAIO; CHARÃO MARQUES, JULIANA; COSTA, JORGE ALBERTO (Pesquisas em Geociências, 2007)
<!– .p text-align: justify; –> The hydrothermal alteration associated with the tin mineralization in the Encruzilhada do Sul Tin District is characterized by zones with different compositions. The most important of these hydrothermal zones are the phyllic and the argillic. The first one is composed mainly by white mica and quartz with tourmaline. The argillic alteration is composed by kaolinite. The phyllic zones represent associations with greisens and disseminated pervasive white mica on the granitic wall rocks. The argillic zones are constrained to the top zones of some granitic intrusions associated with greisens and quartz-veins in the stockworks. The hydrothermal fluids associated with the alteration show homogenization temperatures ranging from about 450˚C to 120˚C. The first temperature is the upper limit for the hydrothermal system, related with the white mica high temperature alteration. The second temperature is the lower limit of the argillic alteration under the hydrothermal conditions. The white mica related with the phyllic alteration range from phengite to muscovite. The argillic alteration has the presence of halloysite, probably as a weathering product.